Behavior of residual soil with high silt content under low frequency cyclic loading using modified direct simple shear apparatus - Sivadass Thiruchelvam; Kamal Nasharuddin Mustapha; Lee, Choon Yong; Rahsidi Sabri Muda (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents the experimental work on typical Malaysian silty residual soils in order to evaluate fundamental soil properties in particular its stiffness under low frequency cyclic loading. There has been very little information on local silty residual soils which is very important for local geotechnical design purposes. Lack of such information contributes to the dependency of foreign soil data which might not be representative of local silty residual soils. This study departs from the basis of there have been verified evidences that we are not spared from seismic activity in Malaysia. Hence, it would be misleading if we were to exclude soil properties under cyclic loading for design purposes in Malaysia. This research revolves around the development of simplified device to evaluate the stress-strain behaviour of soils under simple shear strain conditions. The cyclic loading test results on Malaysian sedimentary residual soil sample exhibit increase of drained shear stiffness, GSTIF and gained strength after 30 cycles indicating cyclic hardening behaviour. It is evident that magnitudes of cyclic load and cyclic displacement influences the rate of soil volume change. Nevertheless, the densification of soil samples due to increment of cycles caused reduction in volume change. It is foreseen that the obtained parameters could assist in the practical geotechnical engineering problems related to cyclic conditions.